An integrated micromorphological and phytolith study of urban soils and sediments from the Gallo‐Roman town Atuatuca Tungrorum, Belgium. Issue 4 (17th January 2019) - Wouters, Barbora; Devos, Yannick; Vrydaghs, Luc; Ball, Terry; De Winter, Natasja; Reygel, Patrick
Abstract: Tongeren is the only Roman administrative capital within the borders of present‐day Belgium. It developed in the first century A.D. and became an important civitas . Many excavations in the center of town have uncovered complex stratigraphic sequences, including dark earths, dating to Roman as well as early medieval times. Their interpretation, based on traditional archaeological methods, often remains problematic. A large‐scale excavation at Vermeulenstraat in 2014 is the first occasion where a geoarchaeological study was conducted using both micromorphology and the study of phytoliths in thin sections. The aim was to evaluate the impact of depositional and post‐depositional processes, to gain an understanding of the formation of the dark earths encountered on the site, to characterize the deposits between and underneath them, and to identify and differentiate human activities and natural phenomena. The results show a range of different activities and events, such as cultivation, construction (including floor preparation), destruction, waste dumping, and gardening. Their different formation histories illustrate the evolution of the area, and their analysis provides an important precedent for the further geoarchaeological study of this town.